Colleters in American Spermacoceae Genera of Rubiaceae: morphoanatomical and evolutionary aspects - Judkevich, Marina Daniela (2017)
Premise of research: The primary goal of this study is to describe the colleters on vegetative and reproductive organs in the Spermacoceae tribe and to characterize their morphoanatomy, their distribution, and some functional and evolutionary aspects. Methodology: The anatomy, development, and vascularization of colleters from 28 species were studied using standard light and scanning electron microscopy based on fresh and fixed material. Our results are interpreted within the framework of recent molecular phylogenies. Pivotal results: Standard-type colleters were found on stipules, calyx, and bracteoles, and they were also found on underground buds in five species of Galianthe. Six species have green colleters, and two have vascularized colleters. We discuss previously unknown functional aspects based on the Staelia glandulosa colleters and propose a new term: long-lived colleters. Conclusions: This article describes the anatomy of colleters in the Spermacoceae tribe of the family Rubiaceae in detail. The presence of underground colleters in Galianthe grandifolia is confirmed and extended to other species of the genus. Vascularization is recorded for the first time in colleters of Mitracarpus and Staelia. This study provides data about the type, distribution, and anatomy of colleters in Spermacoceae, contributing important information for ongoing phylogenetic studies in the tribe. The proposal of a new functional type of colleter based on anatomical, morphological, and ecological aspects, named long-lived colleter, reflects the need to perform further comprehensive studies based on multidisciplinary approaches.